Exploring the Role of Competence and Training in Enhancing Employee Performance: The Mediating Effect of Job Satisfaction Among University Staff in Pekanbaru - Putri, Lidya Anisa; Karya , Detri (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the impact of competence and training on employee performance in higher education institutions in Pekanbaru, with a focus on job satisfaction as a mediating variable. Using a quantitative approach and data collected through structured surveys, the research examines the relationships among these variables. The findings reveal that both competence and training significantly influence employee performance, with job satisfaction playing a critical role in mediating these effects. The results indicate that as employees' competencies and training opportunities increase, so does their job satisfaction, which in turn enhances their overall performance. This research underscores the importance of implementing effective training programs and fostering employee competence to improve performance outcomes in higher education settings. The implications of these findings suggest that universities should prioritize employee development initiatives to achieve organizational goals and enhance the quality of education.